THE SOCIO-CLINICAL IMPACT OF GLP-1 RECEPTOR AGONISTS ON ORAL HEALTH: BRIDGING THE BIOPSYCHOSOCIAL GAP THROUGH DIGITAL HEALTH TECHNOLOGIES - Krzyżanowska, Marta; Smyczyńska , Natalia; Jankowska , Natasza; Trochim , Sebastian; Kubik, Mikołaj; Curzytek , Kacper (International Journal of Innovative Technologies in Social Science, 2026)
The exponential global adoption of glucagon-like peptide-1 receptor agonists (GLP-1 RAs) for metabolic management has inadvertently unmasked a secondary crisis within the oral-systemic axis. This systematic review aims to synthesize the clinical pathophysiology of GLP-1 RA-induced oral dysfunction and evaluate its broader biopsychosocial and economic impacts, proposing digital health interventions as a mitigating framework. Utilizing a multi-stage search strategy across PubMed/MEDLINE, Scopus, Web of Science, and the Cochrane Library (up to 2025), 34 out of 142 screened sources were selected for high-level synthesis. Findings indicate that GLP-1 RAs disrupt salivary homeostasis by down-regulating aquaporin-5 and inducing secondary gastroesophageal reflux, precipitating rapid perimylolysis, xerostomia, and dysgeusia. Beyond physiological damage, this localized deterioration acts as a severe psychosocial stressor, driving social isolation, elevated anxiety, and occupational presenteeism, fundamentally altering the depreciation rate of the patient’s "Health Capital". The current siloed architecture of medical and dental care fails to address this multifaceted burden. The review concludes that a paradigm shift toward Value-Based Healthcare is imperative. By embedding digital health interventions—such as continuous Internet of Things (IoT) salivary biomonitoring, Artificial Intelligence (AI) diagnostic screening, and teledentistry—into a mandatory "Diabeto-Dental Care Pathway," reactive interventions can be replaced with proactive prevention. Bridging the medical-dental divide through technology and enhanced eHealth literacy is essential to safeguard the socio-economic vitality of patients undergoing incretin therapies.